Fine‐tuning the 'plant domestication‐reduced defense' hypothesis: specialist vs generalist herbivores. Issue 1 (6th September 2017) - Gaillard, Mickaël D. P.; Glauser, Gaétan; Robert, Christelle A. M.; Turlings, Ted C. J.
Summary: Domesticated plants are assumed to have weakened chemical defenses. We argue, however, that artificial selection will have maintained defense traits against specialized herbivores that have coexisted with the crops throughout their domestication. We assessed the performance of eight species of insect herbivores from three feeding guilds on six European maize lines and six populations of their wild ancestor, teosinte. A metabolomics approach was used in an attempt to identify compounds responsible for observed differences in insect performance. Insects consistently performed better on maize than on teosinte. As hypothesized, this difference was greater for generalist herbivores that are normally not found on teosinte. We also found clear differences in defense metabolites among the different genotypes, but none that consistently correlated with differences in performance. Concentrations of benzoxazinoids, the main chemical defense in maize, tended to be higher in leaves of teosinte, but the reverse was true for the roots. It appears that chemical defenses that target specialized insects are still present at higher concentrations in cultivated maize than compounds that are more effective against generalists. These weakened broad‐spectrum defenses in crops may explain the successes of novel pests.